Identification And Speciation Of Acinetobacter And Their Antimicrobial Susceptibility Testing - Preeti B. Mindolli*, Manjunath P. Salmani, Vishwanath G and Hanumanthappa A.R (Al Ameen Journal of Medical Sciences, 2010)
Acinetobacter has emerged as an important nosocomial pathogen. Although obvious in nature, it is commonly seen in hospital environment causing many outbreaks of diseases. A study was conducted in which a total of 4696samples, out of which 536 were nonfermenters, among these 200 Acinetobacter isolates were isolated. Speciation was done which showed Acb complex 156 (78%), A. lwoffii 25 (12.5%), A. hemolyticus 12 (06%), A. junii 06 (03%), A. radioresistens 01 (0.5%). Resistance pattern to various drugs were Meropenem 19 (9.5%), Piperacillin-tazobactum 19 (9.5%), Netilmicin 61 (30.5%), Amikacin 75 (37.5%), Ceftazidime 77 (38.5%), Gentamicin 95 (47.5%), Ofloxacin 147 (73.5%), Chloramphenicol 175 (87.5%).